Altered Cingulum Functioning in Major Depressive Disorder Patient With Suicide Attempts: A Resting-State Functional Magnetic Resonance Imaging Study - Yang, Chunxia; Duan, Yajuan; Lei, Lei; Liu, Penghong; Zhang, Aixia; Li, Gaizhi; Sun, Ning; Wang, Yikun; Liu, Zhifen; Zhang, Kerang (Frontiers in Neuroscience, 2022)
Background: Major depressive disorder (MDD) with suicide attempts (SA) poses a significant public health issue,. This study aims to identify neurobiological markers for MDD with SA on resting-state brain functional magnetic resonance imaging (rs-fMRI). Methods: Fifty‐one unmedicated adult MDD participants (OR: patients), 27 with SA on the Beck Scale for Suicidal Ideation and 24 without SA, underwent rs-fMRI scanning. A group of 30 healthy controls (HC) matched for age, gender and education-level with MDD were chosen. Whole brain analysis of regional homogeneity (ReHo) was performed in subjects to identify regions where activity was associated with SA. Multiple comparison analysis was performed for ReHo. Pearson’s correlation analysis was performed between HAMD-SA scores and ReHo. The statistical significance level was set at p < 0.05. Results: We examined whether there were significant differences among the three groups in whole brain ReHo during resting state. Subjects with SA showed significant increase of ReHo in the right Cingulum Post than those without SA in two clusters. Subjects with SA showed significant decrease of ReHo in the right Cingulate Gyrus/ Precuneus than HC. The mean ReHo from the significant clusters was associated with HAMD‐SA scores(r=0.349, P=0.012) and was not associated with HAMD‐24 scores. Conclusions: These results indicate that SA is associated with altered resting‐state brain activity. The pattern of elevated activity in the cingulum functioning may be related to SA. Identifying cingulum activity associated with SA may help to elucidate its pathogenesis and etiology.